Microbe Family Get Away! Storing food smartly & safely - Clark, Mary P.; Peters, Paula; Grover, Phyllis (My University, 1994)
Microbe Family Get Away! is the fourth in a five part program on Safe Food for Children: A series of lessons for parents and child care providers.
L895_1994-11
Keywords: L895; Home and Family; Health and Safety; L